E-Learning Dalam Metode Pembelajaran Pendidikan Agama Kristen Di Era Industrial 4.0 - Gulo, Arifman; Tanasyah, Yusak (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2022)
Indonesia is the world's largest archipelagic country. Education is one aspect of life that can be used to promote and improve the quality of human resources (context of Christian religious education). There are numerous approaches for developing a traditional national education system in the sphere of education, notably teaching, and learning activities in the classroom. However, in the era of industrial digitalization 4.0, the education system that is currently emerging is the e-learning technique and educational information system (online learning) that has no space or time constraints. As a Pancasila State, Christian Religious Education is supposed to color the output of national education and the Church community in Indonesia. It is vital to develop to improve the quality and quantity of Christian Religious Education on a national scale. to improve both the quality and quantity of Christian Religious Education Nationally, it is required to create e-learning (online learning) in Christian schools, Theology schools, and other institutions to reach the Church community in Indonesia's numerous main, small, and distant islands. Especially those who have not been reached by teachers (teachers and lecturers) who are trustworthy and qualified in their professions, so that Christian human resources acquire quality Christian religious education and increase in number nationally. It is desired that millennial Christian human resources will flourish and bear fruit in the Church. Not only must one learn and then bear fruit, but one must also grow closer to God, as well as modify the circumstances, ethics, and Christian character that can provide the best for the development. Indonesia merupakan negara kepulauan terbesar di dunia. Pendidikan merupakan salah satu aspek kehidupan yang dapat digunakan untuk memajukan dan meningkatkan kualitas sumber daya manusia (konteks pendidikan agama Kristen). Ada banyak pendekatan untuk mengembangkan sistem pendidikan nasional tradisional di bidang pendidikan, terutama kegiatan belajar mengajar di kelas. Namun di era digitalisasi industri 4.0, sistem pendidikan yang sedang berkembang saat ini adalah teknik e-learning dan sistem informasi pendidikan (online learning) yang tidak memiliki batasan ruang dan waktu. Sebagai Negara Pancasila, Pendidikan Agama Kristen sudah seharusnya mewarnai output pendidikan nasional dan masyarakat gereja di Indonesia. Sangat penting untuk dikembangkan untuk meningkatkan kualitas dan kuantitas Pendidikan Agama Kristen dalam skala nasional. Untuk meningkatkan kualitas dan kuantitas Pendidikan Agama Kristen Secara Nasional, perlu dibuat e-learning (pembelajaran online) di sekolah-sekolah Kristen, sekolah teologi, dan lembaga lainnya untuk menjangkau komunitas gereja di berbagai pulau utama, kecil, dan jauh di Indonesia. Terutama yang belum terjangkau oleh guru (guru dan dosen) yang amanah dan berkualitas dalam profesinya, sehingga sumber daya manusia Kristen memperoleh pendidikan agama Kristen yang berkualitas dan meningkat jumlahnya secara nasional. Diharapkan sumber daya manusia Kristen milenial tumbuh subur dan berbuah di Gereja. Bukan hanya harus belajar lalu berbuah, tetapi juga harus semakin mendekatkan diri kepada Tuhan, serta mengubah keadaan, etika, dan karakter kristiani yang dapat memberikan yang terbaik bagi perkembangannya.